Moderation-Based Multicultural Education Religious: Challenges and Solutions - Hanum, Azizah; Polem, Suharni; Gea, Yusnidar (Jurnal Dimensi Pendidikan dan Pembelajaran, 2025)
Islam's view on multicultural education and its response to diversity in society, especially in educational institutions, aims to ensure that every ethnic group has equal rights. This research aims to explain how Islam views multicultural education. Using a qualitative approach through a literature study, various references from books, journals, and related research are analyzed in depth. Multicultural education emphasizes equality amidst cultural differences. In Islam, differences are seen not as a source of conflict or a measure of one's nobility, but as an opportunity for mutual understanding and respect. Multicultural education is an important element in maintaining unity and social integration in diverse societies by educating about equality, justice, and respect for different races, ethnicities, languages, traditions, and religious beliefs. This education is in line with Islamic values reflected in the Qur'an, which emphasizes the importance of respecting diversity. The Prophet Muhammad and his companions have also applied this principle, as seen in the Medina Charter.